2023
DOI: 10.1182/bloodadvances.2023009798
|View full text |Cite
|
Sign up to set email alerts
|

Drugs activating hypoxia-inducible factors correct erythropoiesis and hepcidin levels via renal EPO induction in mice

Abstract: The erythroid growth factor erythropoietin (EPO) is mainly produced by the kidneys in adult mammals and induces expansion of erythroid cells and iron use for hemoglobin synthesis. The liver also produces EPO at a lower level than the kidneys. Renal and hepatic EPO production is fundamentally regulated by hypoxia-inducible transcription factors (HIFs) in a hypoxia/anemia-inducible manner. Recently, small compounds that activate HIFs and EPO production in the kidneys by inhibiting HIF-prolyl hydroxylases (HIF-PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Therefore, HIF-PH inhibitors (PHD inhibitors) have been developed to block over-activated PHDs and are currently used for treatment of renal anemia. ( 43 46 )…”
Section: Rep Cells Are Transformed Into Myofibroblasts Thereby Promot...mentioning
confidence: 99%
“…Therefore, HIF-PH inhibitors (PHD inhibitors) have been developed to block over-activated PHDs and are currently used for treatment of renal anemia. ( 43 46 )…”
Section: Rep Cells Are Transformed Into Myofibroblasts Thereby Promot...mentioning
confidence: 99%
“…However, it has been reported that hepcidin is not a direct transcriptional target of HIF [ 21 ]. The mechanism by which hepcidin is decreased by HIF-PHIs has been attributed primarily to increased production of erythroferron due to increased hematopoiesis [ 22 ].…”
Section: Advantages Of and Potential Issues With Hif-phismentioning
confidence: 99%